PENYULUHAN KESEHATAN MENGENAI PENTINGNYA MAKANAN JAJANAN SEHAT DAN BERGIZI PADA SISWA SDN 018 PENYESAWAN - Ade Dita Puteri; Devina Yuristin (Universitas Pahlawan Tuanku Tambusai, 2022)
Food is one of the necessities in human life which is essential for the process of growth and development as well as the basis for maintaining health, both for children and adults. Every food that enters our body can affect metabolism and blood composition in the body. It is not uncommon to find snacks that are traded around the school containing additional substances such as preservatives and food coloring. Snacking habits in children are closely related to the economy and the level of knowledge of children and parents regarding the selection of healthy and nutritious snacks. Community Service provides health education regarding the importance of healthy and nutritious snacks which can be identified in several specific issues, the effect of health education on the importance of healthy and nutritious snacks. The importance of counseling is to increase students' knowledge about the importance of healthy and nutritious snacks for health and to encourage the implementation of a healthy snack program by establishing a canteen that only provides healthy and nutritious snacks. The counseling participants were 78 students of class VI SDN 018 Penyesawan. Keywords : Food, Explanation